Immunmodulatory and Antiproliferative Properties of Rhodiola Species - Recio, Mari-Carmen; Giner, Rosa-María; Máñez, Salvador (Planta Medica, 2016)
The traditional medicines of Asia and Europe have long used various Rhodiola species, which are endemic to the subarctic areas of the northern hemisphere, as tonic, adaptogen, antidepressant, and anti-inflammatory drugs. In order to establish the therapeutic uses of these plants in modern medicine, the pharmacological effects of Rhodiola sp. have been widely studied. Indeed, the most amply researched species, Rhodiola rosea, has been shown to possess antioxidant, adaptogenic, antistress, antimicrobial, immunomodulatory, angiomodulatory, and antitumoral effects. Salidroside (p-hydroxyphenethyl-β-D-glucoside), a major compound in Rhodiola, seems to be responsible for many of the effects observed with Rhodiola extracts.The aim of this paper is to review the pharmacological effects not only of various Rhodiola species, mainly R. rosea along with Rhodiola imbricata, Rhodiola algida, and Rhodiola crenulata, but also of salidroside, focusing especially on its antioxidant, immunomodulatory, antitumoral, and antiproliferative activities, as well as to describe their therapeutic significance in disease management. Although previous pharmacological studies have established a scientific basis for possible therapeutic uses of Rhodiola extracts and salidroside, high-quality, randomized, controlled clinical trials are still needed.
Keywords: Rhodiola - salidroside; adaptatogen; antitumor; immunostimulant; antioxidant